2020
DOI: 10.1073/pnas.1911816117
|View full text |Cite
|
Sign up to set email alerts
|

CD300f immunoreceptor is associated with major depressive disorder and decreased microglial metabolic fitness

Abstract: A role for microglia in neuropsychiatric diseases, including major depressive disorder (MDD), has been postulated. Regulation of microglial phenotype by immune receptors has become a central topic in many neurological conditions. We explored preclinical and clinical evidence for the role of the CD300f immune receptor in the fine regulation of microglial phenotype and its contribution to MDD. We found that a prevalent nonsynonymous single-nucleotide polymorphism (C/T, rs2034310) of the human CD300f receptor cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 70 publications
3
23
1
Order By: Relevance
“…Although SCI did not alter the number of CD11b + CD45 int microglia in the brain at 7 days post-injury, our data indicate that SCI causes maladaptive transformation of microglia in the cerebral cortex from a neurorestorative or neuroprotective phenotype to a neurotoxic phenotype. The latter may contribute to SCI-mediated depressive-like behavior, which is in agreement with a recent study 82 showing similar changes in microglial phenotype can spur the development of neuropsychiatric diseases, including major depressive disorder. Moreover, NanoString analysis demonstrated that SCI decreased 30 out of a total of 44 differentially expressed genes in the cortex, which was strongly related to neurons and neurotransmission, apoptosis, and microglia function.…”
Section: Discussionsupporting
confidence: 92%
“…Although SCI did not alter the number of CD11b + CD45 int microglia in the brain at 7 days post-injury, our data indicate that SCI causes maladaptive transformation of microglia in the cerebral cortex from a neurorestorative or neuroprotective phenotype to a neurotoxic phenotype. The latter may contribute to SCI-mediated depressive-like behavior, which is in agreement with a recent study 82 showing similar changes in microglial phenotype can spur the development of neuropsychiatric diseases, including major depressive disorder. Moreover, NanoString analysis demonstrated that SCI decreased 30 out of a total of 44 differentially expressed genes in the cortex, which was strongly related to neurons and neurotransmission, apoptosis, and microglia function.…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, LTBP-1 targets latent TGF-β1 to the ECM by interacting with different proteins including fibronectin and fibrillin, generating deposits of latent TGF-β1 accessible for cell-mediated activation and regulating cancer cell proliferation and immunity [59]. Immunology homeostasis instabilities may cause deficits of cognitive and memory in human brain, which could be a potential cause of depressive and anxiety disorders [60]. On the other side, as important component of neural microenvironment, ECM could regulate the neural inflammation in central nervous system [61].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, LTBP-1 targets latent TGF-β1 to the ECM by interacting with different proteins including bronectin and brillin, generating deposits of latent TGF-β1 accessible for cell-mediated activation and regulating cancer cell proliferation and immunity [59]. Immunology homeostasis instabilities may cause de cits of cognitive and memory in human brain, which could be a potential cause of depressive and anxiety disorders [60]. On the other side, as important component of neural microenvironment, ECM could regulate the neural in ammation in central nervous system [61].…”
Section: Discussionmentioning
confidence: 99%